2018
DOI: 10.1155/2018/4271497
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Oil Palm Shell Content as Coarse Aggregate in Concrete Based on Mechanical and Durability Properties

Abstract: Oil palm shell (OPS) is a biosolid waste in palm oil industry in the tropical countries which could be used as aggregate in concrete mixture. Since 1984, OPS has been experimented as natural lightweight aggregate in research studies to produce lightweight concrete (LWC). Medium and high-strength LWCs using OPS as coarse aggregate were successfully produced. However, higher drying shrinkage and lower mechanical properties for concretes containing higher volume of OPS are reported in previous studies. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 51 publications
6
11
0
Order By: Relevance
“…For 1:1 1 /2:3 mix ratio, the slump values decreased from 60-18 mm as the PKS contents increased from 0-100%; while for decreased from 40-16 mm for 1:2:4 mix ratio with increase in PKS contents from 0-100% and the slump values of concrete produced with mix ratio 1:3:6 decreased from 30-6 mm as the PKS contents increased from 0-100%. This is corroborated with the findings of Sobuz et al (2014) and Maghfouri et al (2018) where decrease in slump values were observed as PKS contents increases. These results indicate that the presence of PKS and RHA decrease the workability of concrete compared with the control for in workability is attributed the rough texture, irregular, flaky, elongated or angular shape and higher bulk density of PKS compare to granite (Maghfouri et al, 2018).…”
Section: Physical Characteristic Of Aggregatessupporting
confidence: 92%
See 3 more Smart Citations
“…For 1:1 1 /2:3 mix ratio, the slump values decreased from 60-18 mm as the PKS contents increased from 0-100%; while for decreased from 40-16 mm for 1:2:4 mix ratio with increase in PKS contents from 0-100% and the slump values of concrete produced with mix ratio 1:3:6 decreased from 30-6 mm as the PKS contents increased from 0-100%. This is corroborated with the findings of Sobuz et al (2014) and Maghfouri et al (2018) where decrease in slump values were observed as PKS contents increases. These results indicate that the presence of PKS and RHA decrease the workability of concrete compared with the control for in workability is attributed the rough texture, irregular, flaky, elongated or angular shape and higher bulk density of PKS compare to granite (Maghfouri et al, 2018).…”
Section: Physical Characteristic Of Aggregatessupporting
confidence: 92%
“…This is corroborated with the findings of Sobuz et al (2014) and Maghfouri et al (2018) where decrease in slump values were observed as PKS contents increases. These results indicate that the presence of PKS and RHA decrease the workability of concrete compared with the control for in workability is attributed the rough texture, irregular, flaky, elongated or angular shape and higher bulk density of PKS compare to granite (Maghfouri et al, 2018). The reduction of workability of RHA-blended PKSC can also be attributed to the increase in replacement level of PKS having higher fine particles leading to increase in its surface area compared with granite as indicated in the gradation curves (Figure 2) can cause an increase in water demand.…”
Section: Physical Characteristic Of Aggregatessupporting
confidence: 92%
See 2 more Smart Citations
“…There was also aware of using high volume OPS aggregates in concrete mixtures. A recent study [13] on the mechanical and durability properties (in terms of water absorptions and drying shrinkage) of OPS concrete concluded that the volume of coarse OPS aggregate in the concrete mixture should not exceed from 60% of total volume of coarse aggregate. This limitation is due to the fact that concrete containing more than 60% OPS aggregates showed high drying shrinkage.…”
Section: Properties Of Oil Palm Shell Concretes and Some Concernsmentioning
confidence: 99%